Chennakeshava temple, Beluru, The Varaha (boar) avatar of Vishnu, p24 - Brig Ajai Singh (2021)
Image courtesy: Brig A.P. Singh - www.collectingmoments.in; Image courtesy: Brig A.P. Singh - www.collectingmoments.in